Metabarcoding the night sky: Monitoring landscape-scale insect diversity through bat diet - Cynthia Tobisch; Svenja Dege; Bernd Panassiti; Julian Treffler; Christoph Moning (Basic and Applied Ecology)
Widespread declines of terrestrial insects are reported across habitats and are associated with drivers at the landscape scale. Current monitoring schemes survey insect communities mostly at local scales, while assessments of insect trends at the landscape scale are scarce. Insectivorous bats provide a feasible means to tackle this challenge, as they feed opportunistically on a wide variety of insects and other arthropods, while foraging in various habitats and thereby covering large distances between their roosts and hunting places. In this study, we analyzed the diet of a common European bat species (Pipistrellus pipistrellus) to investigate patterns in insect richness and composition at the landscape scale. We collected 24 fecal samples from 12 roosting places in Southern Germany and assessed insect richness and composition using DNA metabarcoding. We explored spatial and temporal variation in the diet of P. pipistrellus and quantified effects of landscape composition and configuration on insect species richness and composition using generalized linear models and non-metric multidimensional scaling. A total of 405 different insect and other arthropod species were identified in the fecal samples, with high proportions of Diptera (45 %), Lepidoptera (18 %), Coleoptera (13 %) and Hymenoptera (11 %), but also many other taxonomic groups. Species composition in the diet showed high variation in space and time, but was also associated with edge density and the proportion of grassland within 2 km radius of the roosts. Moreover, forest and grassland percentages within 2-km buffers around the roosts significantly increased species richness within the diet. Our study shows that genetic analysis of bat feces provides an efficient and promising approach to assess insect diversity patterns at the landscape level, and highlights the potential of widespread bat species for the monitoring of terrestrial insects at large scales.